2022
DOI: 10.1007/s11764-022-01280-2
|View full text |Cite
|
Sign up to set email alerts
|

The long-term financial experiences of adolescent and young adult cancer survivors

Abstract: Background Cancer-related financial hardship can negatively impact financial well-being and may prevent adolescent and young adult (AYA) cancer survivors (ages 15–39) from gaining financial independence. This analysis explored the financial experiences following diagnosis with cancer among AYA survivors. Methods We conducted a cross-sectional, anonymous survey of a national sample of AYAs recruited online. The Comprehensive Score for Financial Toxicity (COST) and InChar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In the United States, given the complexity health insurance coverage that requires patients to build a deep knowledge of plan structures and out-of-pocket costs, 3 the increasing shift toward placing financial burden on patients because of increasing out-of-pocket costs, and the continual federal insurance policy changes that can both help 44 and harm 45 patients with cancer, programs such as HIAYA CHAT represent an important strategy to support AYA patients with cancer who can face a lifetime of financial repercussions from their cancer treatment. 46…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, given the complexity health insurance coverage that requires patients to build a deep knowledge of plan structures and out-of-pocket costs, 3 the increasing shift toward placing financial burden on patients because of increasing out-of-pocket costs, and the continual federal insurance policy changes that can both help 44 and harm 45 patients with cancer, programs such as HIAYA CHAT represent an important strategy to support AYA patients with cancer who can face a lifetime of financial repercussions from their cancer treatment. 46…”
Section: Discussionmentioning
confidence: 99%
“…When compared with younger pediatric patients who have cancer, AYAs report greater psychological and financial distress and fewer positive health beliefs and treatment‐adherent behaviors 19–21 . Furthermore, AYAs with cancer have high risks of late and long‐term effects, including financial hardship, cancer‐related infertility, sexual dysfunction, cardiovascular dysfunction, disease recurrence, and second primary cancers 22–27 …”
Section: Overviewmentioning
confidence: 99%
“…[19][20][21] Furthermore, AYAs with cancer have high risks of late and long-term effects, including financial hardship, cancer-related infertility, sexual dysfunction, cardiovascular dysfunction, disease recurrence, and second primary cancers. [22][23][24][25][26][27] Despite these adverse outcomes, AYAs with cancer have a tremendous capacity for positive psychosocial outcomes. In the largest population-based patient experience study of AYAs to date, the National Cancer Institute's AYA Health Outcomes and Patient Experience (AYA HOPE) study, participants reported the coexistence of both negative and positive life changes.…”
mentioning
confidence: 99%
“…A significant barrier to FP services is cost, which can contribute to medical financial toxicity in CAYA survivors. 95 Without benefit mandates, FP costs are high, averaging $10,078 for females and $468 for males, and are typically not covered by health insurance. 96 Increasingly, employers are adding FP benefits to their health insurance plans.…”
Section: Fp Costs and Health Insurance Benefitsmentioning
confidence: 99%